Ornithological code in the contemporary Ukrainian language (on the example of the local literature) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article defines the main types of semantic relations in the analyzed lexical-semantic group according to lexico-graphic sources; analyzes national-semantic specificity of identifiers in accordance with the inner form; examines specificity in development of indirect meanings for birds names in Ukrainian language on the example of author’s literary speech of the native country.
Keywords: lingvoculturological analysis; ornithonim; ornithological code; literary speech; lingual picture of the world; ethnic culture